Analisis Determinan Pembentuk PDRB dalam Perspektif Infrastruktur Publik dan Daya Saing Daerah di Jawa Tengah - Sudardi, Akbar Maulana; Arif, Muhammad (Jurnal Samudra Ekonomi dan Bisnis, 2026)
The study analyzes the influence of infrastructure and the Regional Competitiveness Index (IDSD) on Gross Regional Domestic Product (GRDP) in 13 districts/cities in Central Java Province for the period 2018–2024. The variables analyzed include GRDP as the dependent variable, as well as the number of schools, road length, hospital number, public transportation, market number, and IDSD as independent variables. The research method uses multiple linear regression with panel data, which combines a seven-year time series and cross-section in 13 districts/cities. The results show that infrastructure and IDSD simultaneously have a significant effect on GRDP. Partially, the number of schools, hospitals, and public transportation have a significant positive effect, while the number of markets, road length, and IDSD are not significant. This condition is assumed to be due to the quality of markets and roads not optimally driving regional productivity. These findings provide important insights for the equitable distribution of regional economic contributions.